2003
DOI: 10.1086/379792
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Intermediate Charcot-Marie-Tooth Type C Maps to Chromosome 1p34-p35

Abstract: Dominant intermediate Charcot-Marie-Tooth (DI-CMT) neuropathy is a genetic and phenotypic variant of classical CMT, characterized by intermediate nerve conduction velocities and histological evidence of both axonal and demyelinating features. We report two unrelated families with intermediate CMT linked to a novel locus on chromosome 1p34-p35 (DI-CMTC). The combined haplotype analysis in both families localized the DI-CMTC gene within a 6.3-cM linkage interval flanked by markers D1S2787 and D1S2830. The functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 40 publications
2
40
0
5
Order By: Relevance
“…Three types of dominantly inherited CMT with intermediate MNCV had been identified. CMTDI2 was linked to chromosome 10q24.1-q25.1 [10][11][12], DI-CMTC was linked to chromosome 1p34-p35 [13], and DI-CMTB was linked to chromosome 19p12-13.2 [14,15]. Mutations had been identified in DNM2 gene for DI-CMTB [5].…”
Section: Discussionmentioning
confidence: 99%
“…Three types of dominantly inherited CMT with intermediate MNCV had been identified. CMTDI2 was linked to chromosome 10q24.1-q25.1 [10][11][12], DI-CMTC was linked to chromosome 1p34-p35 [13], and DI-CMTB was linked to chromosome 19p12-13.2 [14,15]. Mutations had been identified in DNM2 gene for DI-CMTB [5].…”
Section: Discussionmentioning
confidence: 99%
“…YARS encodes tyrosyl-tRNA synthetase (TyrRS) and is located on chromosome 1p35.1 [44] . Aminoacyl-tRNA synthetases (ARSs) charge amino-acids onto their homologous tRNAs during protein translation.…”
Section: Yars and Di-cmtc Phenotypementioning
confidence: 99%
“…In the North American and the Bulgarian families with YARS mutations, the clinical features were age at onset between 10 and 60 years, intermediate MNCV ranging from 25 to 58 m/s, slow progression, and moderate severity [44] .…”
Section: Jordanova Et Al Reported Two Mutations In Yarsmentioning
confidence: 99%
“…For example, Landsverk et al identified the gene causing a hereditary neuropathy (hereditary neuralgic amyotrophy [HNA]) that attacks the muscles responsible for controlling the movement of shoulders and arms 65 . In addition, Florian Thomas MD (St. Louis University, St. Louis, USA) and his international team have uncovered three different genetic mutations specific to dominant intermediate CMT neuropathy type C, a form of CMT disease 66 . Organizations like The American Association of Neuromuscular and Electrodiagnostic Medicine (AANEM) could be funded to support awarding of fellowships that focus on rare neuromuscular disease research.…”
Section: Introductionmentioning
confidence: 99%